Ultralong Stability of Ti 3 C 2 T x ‐MXene Dispersion Through Synergistic Regulation of Storage Environment and Defect Capping with Tris‐HCl Buffering - Tan, Jiayi; Fan, Baomin; Zhang, Peng; Wei, Yi; Soomro, Razium A.; Zhao, Xiaoqi; Kumar, Jai; Qiao, Ning; Xu, Bin (Small methods, 2024)
Aqueous MXene dispersion suffers from a bottleneck issue of oxidation, leading to its gradual deterioration and ultimately compromised physicochemical characteristics. Herein, Tris‐HCl buffer is employed to stabilize the diluted Ti 3 C 2 T x ‐MXene dispersion (0.05 mg mL −1 ) through the synergy of its potent pH‐regulation capability and capping effect toward oxidation‐susceptible defects/edges. Tris‐HCl functionalized Ti 3 C 2 T x maintained its original morphology, structure, and favorable dispersity even after 150 days of aging under naturally aerated conditions. The pH‐regulation nature of Tris‐HCl is elucidated through solution monitoring of Ti 3 C 2 T x dispersion, while the adsorption of Tris‐HCl onto defects/edges is revealed by spectral analysis and multi‐scale simulations. Tris‐HCl at the neutral pH can bind to the negatively charged basal plane of Ti 3 C 2 T x via + HTris moiety, while the other moiety (Tris) interacts with the exposed edge‐based Ti atoms and/or intrinsic defects, forming a Ti─N bond that prevents MXene from attack by H 2 O and O 2 . Besides, Tris‐HCl stabilized Ti 3 C 2 T x exhibited nearly identical capacitive characteristics to its freshly‐etched counterpart, indicating the minimal impact of Tris‐HCl on electrochemical performance of Ti 3 C 2 T x during long‐term storage. This study provides practical guidance for stabilizing MXene in their native aqueous dispersion without compromising the inherent properties.